Chlamydia pneumoniae Infects and Multiplies in Lymphocytes In Vitro - Haranaga, Shusaku (American Society for Microbiology, 2001)
The obligate intracellular pathogen Chlamydia (Chlamydophila) pneumoniae is known to be associated with some chronic inflammatory diseases, such as atherosclerosis. Interaction between C. pneumoniae and immune cells is important in the development of such diseases. However, susceptibility of immune cells, particularly lymphocytes, to C. pneumoniae infection has not been reported, even though lymphocytes play a pivotal role in the development of the diseases caused by this bacterium. In this regard, we examined the susceptibility of lymphocytes to C. pneumoniae infection in vitro. The results demonstrated that human peripheral blood lymphocytes as well as mouse spleen lymphocytes could be infected with C. pneumoniae. Furthermore, purified T lymphocytes as well as established T-lymphocyte cell line cells showed an obvious susceptibility to C. pneumoniae infection, indicating that T cells could be one of the host cells for this bacterial infection. These findings reveal a new infection site for C. pneumoniae, i.e., lymphocytes.